Hematological profile of water buffaloes: age and sex-related variations - Jaramillo, Ingrid; Agudelo-Florez, Piedad; Tobón, Julio César; Didier Ruiz, Jhon (Brazilian Journal of Veterinary Pathology, 2024)
The aim of this study was to establish blood reference intervals (RIs) and describe the effects of age and sex. In this cross-sectional study, we analyzed 1225 water buffaloes with nonvisible clinical signs of disease stratified by age and sex. The confidence intervals were calculated for each reference limit (95%, p